Electrochemically induced metal- vs. ligand-based redox changes in mackinawite: identification of a Fe3+- and polysulfide-containing intermediate. Issue 34 (4th August 2021) - Sanden, Sebastian A.; Szilagyi, Robert K.; Li, Yamei; Kitadai, Norio; Webb, Samuel M.; Yano, Takaaki; Nakamura, Ryuhei; Hara, Masahiko; McGlynn, Shawn E.
Abstract : Detection of Fe 3+ and polysulfides during FeS oxidation revealing both metal, and ligand oxidation paths en route to the formation of greigite and pyrite. Abstract : Under anaerobic conditions, ferrous iron reacts with sulfide producing FeS, which can then undergo a temperature, redox potential, and pH dependent maturation process resulting in the formation of oxidized mineral phases, such as greigite or pyrite. A greater understanding of this maturation process holds promise for the development of iron-sulfide catalysts, which are known to promote diverse chemical reactions, such as H +, CO2 and NO3 − reduction processes. Hampering the full realization of the catalytic potential of FeS, however, is an incomplete knowledge of the molecular and redox processess ocurring between mineral and nanoparticulate phases. Here, we investigated the chemical properties of iron-sulfide by cyclic voltammetry, Raman and X-ray absorption spectroscopic techniques. Tracing oxidative maturation pathways by varying electrode potential, nanoparticulate n (Fe 2+ S 2− )(s) was found to oxidize to a Fe 3+ containing FeS phase at −0.5 V vs. Ag/AgCl (pH = 7). In a subsequent oxidation, polysulfides are proposed to give a material that is composed of Fe 2+, Fe 3+, S 2− and polysulfide (S n 2− ) species, with its composition described as Fe 2+ 1−3 x Fe 3+ 2 x S 2− 1− y (S n 2− ) y . Thermodynamic properties of model compounds calculated by density functional theory indicate that ligand oxidation occurs in conjunction with structural rearrangements, whereas metal oxidation may occur prior to structural rearrangement. These findings together point to the existence of a metastable FeS phase located at the junction of a metal-based oxidation path between FeS and greigite (Fe 2+ Fe 3+ 2 S 2− 4 ) and a ligand-based oxidation path between FeS and pyrite (Fe 2+ (S2 ) 2− ).